Creutzfeldt–Jakob disease associated with a T188K homozygous mutation in the prion protein gene: a case report and review of the literature. Issue 1 (31st December 2022) - Shan, Yuheng; Zhang, Jiatang; Cen, Yuying; Xu, Xiaojiao; Tan, Ruishu; Zhao, Jiahua; Yu, Shengyuan
ABSTRACT: Genetic Creutzfeldt–Jakob disease (gCJD) is a prion disease caused by mutations in the prion protein gene ( PRNP ). It has an autosomal dominant inheritance, so gCJD with homozygous mutations is extremely rare, and the influence of homozygous mutations on the gCJD phenotype is unknown. We describe the clinical and laboratory features of a patient with a PRNP T188K homozygous mutation and perform a literature review of gCJD cases with PRNP homozygous mutations. The patient was presented with cerebellum symptoms, cognitive decline and visual disturbances. Auxiliary examinations revealed restricted diffusion in magnetic resonance imaging and glucose hypometabolism on 18 Fluorodeoxyglucose-positron emission tomography. No periodic sharp wave complexes were detected in electroencephalography, and the cerebrospinal fluid 14-3-3 protein was negative. PRNP sequencing revealed the presence of a homozygous T188K variant. The patient died 15 months after disease onset. A literature review revealed PRNP V203I, E200K and E200D as the only three mutations reported as homozygous in gCJD. To the best of our knowledge, this is the first report of a gCJD patient with a PRNP T188K homozygous mutation. Although the clinical manifestations of our patient were similar to those with PRNP T188K heterozygous mutations, she presented with a slightly earlier onset and had a longer survival time. This is consistent with previous observations from patients with PRNP V203I and E200K homozygous mutations. Further studies are essential to clarify the influence of homozygous mutations on the gCJD phenotype.